Agent Communication Strategy to Prospective Customers in Marketing Prucinta Products at PT Prudential Syariah Binjai - Al Tasya Fitrah; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The purpose of this study is to find out how the agent's communication process in marketing insurance products has an effect on buying motivation by prospective customers. Through the use of qualitative descriptive research methods. data collection method using interviews, and collecting some insights from the literature, which focuses on the steps in describing the strategy directed by PT. Prudential Syariah Binjai which will increase its customers. So the search results show that, in the Prucinta Product Marketing communication strategy, PT. Prudential Syariah Binjai, they use a marketing communication strategy to attract potential customers, so that potential customers are influenced and know more and feel confident about Prucinta's products as a guarantee in the future, we can see beliefs and actions that are seen as guidelines. Therefore, agents must carry out two-way communication with prospective customers to get decisions and influence trust by using effective communication to achieve the goal of designing and socializing about insurance so that public understanding about insurance increases.